Sistem Bilangan dan Makna Simbolik dalam Upacara Adat Pernikahan Dayak Iban - claudia gita asri; Flesia Welly Ferianti (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
This study aims to describe the number system used in the traditional wedding ceremony of the Dayak Iban community in Porau Pumpoi Hamlet, West Kalimantan, and to uncover the symbolic meanings embedded within it. The research employs a qualitative descriptive approach from an ethnomathematical perspective. Data were collected through observation, semi-structured interviews with eleven informants consisting of traditional leaders, customary chiefs, community elders, and family members who had witnessed traditional weddings, as well as documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the number system is applied across various stages of the ceremony, with numbers such as 1, 3, 7, and 14 functioning not only as counting tools but also as carriers of symbolic meaning. The number three symbolizes the relationship between humans and God, fellow beings, and nature; the number seven represents perfection and sacredness; while the number fourteen serves as a refinement of the number seven. These findings reflect mathematical concepts such as cyclical patterns, multiples, and ordinal and cardinal systems that are integrated into the local wisdom of the Dayak Iban community. This study contributes to the documentation of Dayak Iban ethnomathematics and provides a contextual mathematics learning resource based on local culture.Keywords: ethnomathematics, number system, symbolic meaning, traditional wedding ceremony, Dayak Iban.